Soils containing sclerotia of Sclerotium rolfsii were covered with transparent plastic and exposed to sunlight in an experiment to study the effect of soil solarization on the growth of the fungi and its pathogenicity to peanut. Soil solarization for 3 to 4 weeks significantly suppressed the sclerotial germination up to 44% and reduced hyphal growth and pathogenicity of S. rolfsii placed at 0.5 cm below the soil sulfate, but did not have any gects when the sclerotia were placed at the depth of 1 - Kartini .; Widodo . (Buletin Hama dan Penyakit Tumbuhan, 2000)
Soils containing sclerotia of Sclerotium rolfsii were covered with transparent plastic and exposed to sunlight in an experiment to study the effect of soil solarization on the growth of the fungi and its pathogenicity to peanut. Soil solarization for 3 to 4 weeks significantly suppressed the sclerotial germination up to 44% and reduced hyphal growth and pathogenicity of S. rolfsii placed at 0.5 cm below the soil sulfate, but did not have any gects when the sclerotia were placed at the depth of 15 cm. Among ungerminated sclerotia, 88.0 and 82.7% of them were physically damaged by 3 and 4 weeks of soil solarization, respectively. Some of the damaged sclerotia were colonized by microorganism. The most frequent colonizing microorganisms observed were Asagillus spp, Trichodenna spp., and bacteria. Increased soil temperature as direct effect of soil solarization and the role of some soil microbes might be responsible for the suppression.